A case of parvovirus infection in a dog - Noor, Faridah; Ibrahim, A. Latif; Tan , Saw Eng; Lai, Chooi May (Persatuan Doktor Veterinar Malaysia, 1980)
A typical case of parvovirus infection in a 4 month old male German Shepherd is reported. The disease is characterised by depression, pyrexia, vomiting and diarrhoea. Electron microscopic examination of faeces from the sick dog revealed the presence of particles resembling paroooirus.